Hydrogen peroxide as a mitigator of salt stress for melon seed germination - Rocha Limão, Marcelo Augusto; Batista Silva Rodrigues, Marília Hortência; da Silva Santos, Adriana; da Silva Barbosa, Luana; Pinheiro Lopes, Kilson; Cunha Fernandes dos Santos Dias, Denise (Comunicata Scientiae, 2022)
The effect of hydrogen peroxide has been very studied, but little is known on its effect on seed germination and initial growth of melon trees under salt stress. In this context, the objective of this work was to evaluate the effect of hydrogen peroxide as a mitigator of salt stress on melon seed germination. The experiment was conducted in the Laboratory of Seeds and Seedlings of the Federal University of Campina Grande, in Pombal, PB, Brazil. A completely randomized design was used, in a 4×6 factorial arrangement consisting of times of seed imbibition in H2O2 (0, 8, 16, and 24 hours) and irrigation water salinity levels (0.3, 1.2, 2.1, 3.0, 3.9, and 4.8 dS m-1), with four replications. Melon seeds of the commercial variety Imperial-45 were used. The H2O2 solution was prepared from a 1 mmol L-1 H2O2 solution, which was diluted to reach the concentration of 10 μmol L-1. The seeds were placed in a beaker and subjected to imbibition with 100 ml of the solution for the different times studied. The variables evaluated were: germination percentage, first germination counting, germination speed index, mean germination speed, mean germination time, and radicle length. The of H2O2 solution to seeds for 16 hours mitigates the negative effects caused by salt stresses by up to 2.2 dS m-1; however, the application of H2O2 solution for 24 hours is harmful to the germination process of melon seeds.